Evaluation of Anti-Tussive Effect of Ardraka Paka and its Modified Syrup in Sulphur Dioxide Induced Cough Model - Nayana N; Krishnamurthy MS; Ravi Rao S (RGUHS Journal of AYUSH Sciences)
Background Ardraka Paka is a classical Guda Paka formulation mentioned in Yogachintamani Ayurveda Sara Sangraha and Bharath Bhaishajya Rathnakara. The pharmaceutical modification of such classical formulations into more convenient dosage forms is the present day need. This approach not only facilitates global acceptance but also enhances therapeutic efficacy and improves patient compliance through convenient mode of administration. The present study focused on evaluating the anti-tussive effects of Ardraka Paka and its modified formulation Ardraka Paka syrup. Objectives To evaluate the anti-tussive effects of Ardraka Paka and Ardraka Paka syrup using the sulphur dioxide SO2 induced cough model.Methods The anti-tussive effects were evaluated using the SO2-induced cough model in albino rats based on the method described by Miyagoshi et al. 1986 with appropriate modifications and simplifications.Results The study findings indicate that both the test drugs Ardraka Paka ADP and Ardraka Paka syrup ADS demonstrated a reduction in the number of cough bouts. The standard group exhibited a 49.25 reduction while the ADP and ADS groups showed reductions of 7.57 and 31.44 respectively. Conclusion The test drug Ardraka Paka syrup showed a statistically significant P lt0.01 reduction in the number of cough bouts proving its potential anti-tussive activity. It was found to be more effective in reducing the frequency of cough bouts compared to Ardraka Paka.